Logistics and supply chain related issues faced by Malaysian SMEs: A case study - Nik Abdullah, Nik Ab. Halim; Yaakub, Sabariah; Subhan, Muhammad (2016)
This study uses a case study approach in order to identify the logistics and supply chain related issues faced by small and medium enterprises(SMEs) in Malaysia.Previous study revealed that the causes of the failure of SMEs are both internal and external and one of the external factors identified are non-availability or deficiency in logistics and supply chain management. Based on these findings, this study is conducted in order to further focus on the logistics and supply chain related issues.Thus, the objective of this study is to identify the logistics and supply chain issues faced by SMEs in Malaysia.Data were collected through case study interviews with five SMEs.The case study interviews reveal two most common issues confronted by these firms, namely customer service and inventory management issues.These two issues are related to one another as lack of inventory will lead to SMEs inability to fulfill their customer needs.Firms themselves need to rectify these issues as they may result in loss of sales, which will eventually result in loss of customers. The finding also indicates the important role of external supply chain members such as the supplier, carrier or third-party logistics service providers as they directly influence the level of customer services provided by SMEs.